The Association Between Cardiovascular Function, Measured as FMD and CVC, and Long-Term Aquatic Exercise in Older Adults (ACELA Study): A Cross-Sectional Study - Klonizakis, Markos; Hunt, Beatrice E.; Woodward, Amie (Frontiers in Physiology, 2020)
Introduction. Cardiovascular ageing is implicated in the development of cardiovascular disease (CVD). Aquatic exercise is being considered as a co-adjuvant form of rehabilitation, but there is limited evidence for its cardiovascular risk-reduction properties for older people. Our study aimed to address this by exploring the cardiovascular effects of long-term aquatic exercise in older adults in comparison to those who are either inactive or engaged in land-based/mixed training by measurement of micro- and macro-circulation. Flow Mediated Dilatation (FMD) was the primary outcome. Methods. This was a pragmatic, 4-group, cross-sectional study. Eighty normotensive adults constituted four (n=20) groups. The Aqua group (aged 63.7 ± 7 years) and Land group (aged 65 ± 6 years) consisted of participants engaged in aquatic and land-based training, respectively. The mixed group (Mix) (aged 66 ± 6 years) consisted of participants engaged in both land-based and aquatic training. Self- reported training consisted of ≥2/week for ≥6 months (mean sessions/week = 4±1, 4±1, and 5±2 for each group, respectively). The sedentary group (Sed) (aged 63 ± 6 years) consisted of people who were sedentary for ≥6 months (mean sessions/week 0±0). The primary outcome was %FMD. Secondary outcomes included raw cutaneous vascular conductance (CVC) and CVC max. Results. Statistically significant differences (%FMD, raw CVC variables other than baseline) were found between each of the exercise groups (Aqua, Land, Mix) and the sedentary group (Sed) (i.e., 12.5 (4.5) vs 5.0 (2.3); p< .0005, between the Aqua group and Sed group, for %FMD). No specific advantage could be attributed to any one of the exercise groups. Conclusions. We reported improvements in NO-mediated endothelial function at micro- and macro-circulatory levels, observing no differences between exercise modes. Our findings provide evidence for the role of aquatic exercise as a “shield” against CVD in older populations.